2017
DOI: 10.1136/gutjnl-2017-314098
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory NK cells mediated between immunosuppressive monocytes and dysfunctional T cells in chronic HBV infection

Abstract: Background and aimsHBV infection represents a major health problem worldwide, but the immunological mechanisms by which HBV causes chronic persistent infection remain only partly understood. Recently, cell subsets with suppressive features have been recognised among monocytes and natural killer (NK) cells. Here we examine the effects of HBV on monocytes and NK cells.MethodsMonocytes and NK cells derived from chronic HBV-infected patients and healthy controls were purified and characterised for phenotype, gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 57 publications
(49 reference statements)
7
118
1
Order By: Relevance
“…Further, we illustrate that increased production of IL‐10 and TGF‐β inhibits the function of CD56 − CD16 + NK cells on CD8 + T cells in HIV‐infected individuals. Similar to our results, Li et al . found that during HBV infection, IL‐10 producing NK cells could inhibit T cell function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, we illustrate that increased production of IL‐10 and TGF‐β inhibits the function of CD56 − CD16 + NK cells on CD8 + T cells in HIV‐infected individuals. Similar to our results, Li et al . found that during HBV infection, IL‐10 producing NK cells could inhibit T cell function.…”
Section: Discussionsupporting
confidence: 93%
“…During mouse cytomegalovirus infection, mouse total NK cells secrete IL‐10, leading to reduced IFN‐γ production by CD8 + T cells . In addition, HBV‐induced NK cells inhibit IFN‐γ production by autologous CD8 + T cells in an IL‐10‐dependent manner . Moreover, total NK cells exhibit negatively regulatory functions in infected individuals; we observed that CD56 − CD16 + NK cells produced more IL‐10 and TGF‐β in HIV‐infected individuals, and our data demonstrate that CD56 − CD16 + NK cells can inhibit IFN‐γ production by CD8 + T cells, the major effector cells against HIV infection.…”
Section: Discussionmentioning
confidence: 60%
“…Further studies will be needed to test if this also applies to exhausted NK cells in the context of chronic infection. A recent paper described that exhausted NK cells in HBV individuals express lower levels of T‐BET mRNA than NK cells from healthy donors , which is a first hint that similar exhaustion mechanisms may be at play in NK and T cells during chronic infections.…”
Section: Introductionmentioning
confidence: 98%
“…This phenotype was similar in monocytes‐derived macrophages . Li et al suggested that HBsAg enabled monocytes to highly express cell surface inhibitors (PD‐L1 and HLA‐E) and anti‐inflammatory factors (TNF‐α, TGF‐β and IL‐10) to interact with NK cells, which led to regulatory NK cells differentiation, further inhibited T‐cell activation.…”
Section: Relationship Between Host and Hbvmentioning
confidence: 83%